2011
DOI: 10.1099/vir.0.037648-0
|View full text |Cite
|
Sign up to set email alerts
|

Replication-incompetent influenza A viruses that stably express a foreign gene

Abstract: A biologically contained influenza A virus that stably expresses a foreign gene can be effectively traced, used to generate a novel multivalent vaccine and have its replication easily assessed, all while satisfying safety concerns regarding pathogenicity or reversion. This study generated a PB2-knockout (PB2-KO) influenza virus that harboured the GFP reporter gene in the coding region of its PB2 viral RNA (vRNA). Replication of the PB2-KO virus was restricted to a cell line stably expressing the PB2 protein. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
80
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 21 publications
4
80
0
Order By: Relevance
“…AX4 cells, which are an MDCK-derived cell line with enhanced expression of human-type receptors for influenza virus and were produced by stable transfection of a plasmid expressing the human ␣-2,6-sialyltransferase (8), were maintained in 5% NCS-MEM supplemented with puromycin (2 g/ml). AX4/ PB2 cells (AX4 cells stably expressing the PB2 protein derived from A/Puerto Rico/8/34 [H1N1, PR8], established by transduction with a retroviral vector [16]) were maintained in 5% NCS-MEM supplemented with puromycin (2 g/ml) and blasticidin (10 g/ml). All cells were maintained in a humidified incubator at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…AX4 cells, which are an MDCK-derived cell line with enhanced expression of human-type receptors for influenza virus and were produced by stable transfection of a plasmid expressing the human ␣-2,6-sialyltransferase (8), were maintained in 5% NCS-MEM supplemented with puromycin (2 g/ml). AX4/ PB2 cells (AX4 cells stably expressing the PB2 protein derived from A/Puerto Rico/8/34 [H1N1, PR8], established by transduction with a retroviral vector [16]) were maintained in 5% NCS-MEM supplemented with puromycin (2 g/ml) and blasticidin (10 g/ml). All cells were maintained in a humidified incubator at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, our group genetically engineered PB2-knockout (PB2-KO) influenza viruses that are able to harbor a reporter gene, such as the green fluorescent protein (GFP) gene, between the packaging signals (the noncoding and coding 120 bases at both the 5= and 3= ends) of the PB2 gene (16). Growth of such PB2-KO viruses is restricted to a cell line stably expressing the PB2 protein and yields high virus titers (Ͼ10 8 PFU/ml).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By using these tandem reporter plasmids instead of an intact PB2 vRNA-expressing plasmid, we generated PB2-knockout viruses by means of reverse genetics. We then counted the GFP-and/or DsRed-positive plaques formed by the transfectant viruses in PB2 protein-expressing MDCK cells that were established by using a retrovirus vector as described previously (16). Like the NA-knockout viruses, these PB2-knockout viruses mainly formed plaques expressing only either GFP (75.6%) or DsRed (23.8%); only a limited portion (0.6%) of the plaques expressed both GFP and DsRed (Fig.…”
mentioning
confidence: 99%
“…Such a packaging signal, which is necessary for viral genome segment-specific packaging, was believed to reside in both the 3= and 5= ends of the noncoding regions (NCRs) and the adjacent terminal coding region of each RNA segment (26)(27)(28)(29)(30)(31)(32)(33)(34). It was demonstrated that foreign genes or influenza virus genes from different types and subtypes could be efficiently cloned between the packaging signals of different influenza virus genes and expressed in the form of proteins (34)(35)(36) (35,37,38). These approaches resulted in the generation of replication-deficient recombinant influenza virus.…”
mentioning
confidence: 99%